Hoaxes, Counter-Information, and the Unequal Governance of Public Information in the Technoculture Era - Eko Setiawan; Rachmah Ida; Irfan Wahyudi (Publisia: Jurnal Ilmu Administrasi Publik, 2026)
The labeling of hoaxes by state authorities over data breach claims does not merely serve as an informational correction; it operates as a mechanism for regulating epistemic authority in the digital space. This article analyzes how hoax formation and the circulation of counter-information on social media function as expressions of digital counterculture within the frameworks of technoculture and the Social Construction of Technology (SCOT), and how these dynamics reflect unequal governance of public information in Indonesia. This study employs a qualitative approach with a case study design and discourse analysis. Data were collected purposively from social media content, digital news coverage, official government statements, and interviews with personnel from the National Police Cyber Unit (Siber Polri), the National Cyber and Crypto Agency (BSSN), and the Ministry of Communication and Information (Kominfo) as state actors, as well as white hacker and black hacker communities. Analysis proceeded through data reduction, thematic coding, narrative categorization, discourse analysis, and theory-driven interpretation using technoculture and SCOT, validated through source triangulation. Findings indicate that hoax labeling serves a dual function as an instrument of epistemic control; counter-information emerges in response to a crisis of public trust and unequal information access; and interpretative flexibility among state actors, media, cyber communities, and the digital public explains how the meaning of data breaches is contested. These dynamics signal a transition from network society to hyper-information society, a condition in which information overload and the illusion of truth effect blur the boundaries between official information, hoaxes, and counter-information